2021
DOI: 10.1108/bjm-03-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Career satisfaction, subjective well-being and turnover intention: an attachment style perspective

Abstract: PurposeOn the basis of an attachment style perspective, the authors explored a moderated mediation model in which career satisfaction reduces employees' turnover intention by enhancing subjective well-being; this mediated relationship would be moderated by three dimensions of attachment style as follows: secure, counterdependent and overdependent.Design/methodology/approachData were collected from 192 employees in South Korea and hypotheses were tested using multiple regression analysis and the PROCESS macro f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The results of the study provided support for this hypothesis as well. Consistent with prior research by Nae and Choi (2022), Akhtar et al (2017) and Ahmad and Kaleem (2019), this study demonstrates that psychological well-being mediates the relationship between job burnout and intentions to change occupation. In other words, when psychological well-being is compromised, job burnout increases the likelihood of intentions to change occupation.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the study provided support for this hypothesis as well. Consistent with prior research by Nae and Choi (2022), Akhtar et al (2017) and Ahmad and Kaleem (2019), this study demonstrates that psychological well-being mediates the relationship between job burnout and intentions to change occupation. In other words, when psychological well-being is compromised, job burnout increases the likelihood of intentions to change occupation.…”
Section: Discussionsupporting
confidence: 89%
“…Only a few delved into the life domain (e.g. Nae and Choi, 2021). Our results supported the spillover theory and extended the understanding of how internal marketing in the work domain is directly and indirectly associated with life satisfaction in nonwork domains.…”
Section: Discussionmentioning
confidence: 99%
“…Unanue et al (2017) revealed the positive link between work and life satisfaction, thus confirming the spillover hypothesis. Similarly, Nae and Choi (2021) asserted that employees satisfied with their career tend to feel high levels of selfefficacy and self-esteem, which enhance satisfaction in life as a whole. Investigating job satisfaction as the connection between work and life domains, Golob and Ponar (2021) supported the direct positive effect of work satisfaction on life satisfaction.…”
Section: H3 Internal Marketing Positively Relates To Life Satisfactionmentioning
confidence: 99%
“…Satisfaction had a strong negative relationship with turnover intention, while well-being remained low. The study by Nae and Choi [23] evidenced the direct relationship between job satisfaction and employee turnover. However, this also pointed out that employee well-being moderates the indirect relationship between job satisfaction and turnover.…”
Section: Plos Onementioning
confidence: 95%